The Role of Phenytoin for Treatment of Enterocutan Fistula in Wistar Rat - Prasetyo , Sigit Adi; Kurniawan , Victor; Irphan , Budiman; Sugiarto , Yohanes; Saragih , Iwan; Pambudi , Gede; Nugroho , Trilaksono; Hardian, .; Hermawan, .; Riwanto , Ignatius (Current Overview on Disease and Health Research Vol. 11, 2023)
Introduction: Enterocutanean fistula (ECF) is a complicated abdominal problem; although spontaneous closure occurs 90% of the time, it takes approximately 5 weeks. Phenytoin was associated with faster pancreatic and enterocutaneous fistula formation. To clarify the mechanism of the healing effect of phenytoin on ECF, animal research will be reported. Methods: The diameter of the ECF, the number of fibroblasts, angiogenesis, the number (percentage) of collagen, the tickness of granulation tissue, and the number of lymphocytes were measured in a randomized controlled trial comparing the ECF of Wistar rats treated with a combination of low-dose phenytoin and vitamin C to phenytoin (oral and topical) or vitamin C alone to a placebo. Results: The diameter of the ECF was significantly (p< 0.05) reduced after high-dose phenytoin treatment and a combination of low-dose phenytoin and vitamin C. High-dose phenytoin or a combination of low-dose phenytoin and Vit C increased the number of fibroblasts, percentage or number of colagen, granulation tissue thickness, and angiogenesis while decreasing the number of lymphocytes (p 0.05). Conclusion: High-dose phenytoin or low-dose phenytoin combined with vitamin C accelerates ECF closure by increasing fibrosis, collagen, angiogenesis, and granulation tissue while decreasing lymphocytes.